2009
DOI: 10.1027/1618-3169.56.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Reasoning as a Heuristic-Based Process

Abstract: The present study interprets the overuse of proportional solution methods from a dual process framework. Dual process theories claim that analytic operations involve time-consuming executive processing, whereas heuristic operations are fast and automatic. In two experiments to test whether proportional reasoning is heuristic-based, the participants solved "proportional" problems, for which proportional solution methods provide correct answers, and "nonproportional" problems known to elicit incorrect answers ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Other lines of research [38,39] demonstrated that in the case of tasks which involved a conflict between a heuristic and a normatively correct response, employing a dual-task load decreased normative performance, and increased participants’ tendency to give a heuristic response. Given that the CRT problems involve a heuristic-normative conflict, we expected that a dual-task load will lead to a reduction in normative responding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other lines of research [38,39] demonstrated that in the case of tasks which involved a conflict between a heuristic and a normatively correct response, employing a dual-task load decreased normative performance, and increased participants’ tendency to give a heuristic response. Given that the CRT problems involve a heuristic-normative conflict, we expected that a dual-task load will lead to a reduction in normative responding.…”
Section: Discussionmentioning
confidence: 99%
“…In our last experiment, we adopted a procedure which was previously used by De Neys [38], and Gillard et al [39]. In these studies, participants had to memorize either simple or complex dot patterns (see Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations